Value stream mapping as a lean manufacturing tool: A new account approach for cost saving in a textile company - Carvalho, C. P. [UNESP]; Carvalho, D. S.; Silva, M. B. [UNESP] (Universitat Politecnica Valencia, 2019)
Companies around the world are under pressure to reduce their prices to be competitive. In order to keep profitability, they are adopting lean manufacturing (LM) and its tools to reduce waste and, consequently, the costs. Value stream mapping (VSM) is an efficient LM tool, identifying production flow waste. When it is possible to combine VSM with other LM tool, such as Kanban, a substantial impact in inventory reduction is reached. Additionally, the conventional account system shows limitations in the costs reduction to keep up with LM. The purpose of this paper is to present the results obtained by the application of the VSM combined with Kanban and the new account approach to measure the effectiveness of the cost reduction in the finished goods inventory. Considering that LM tools application in the textile segment has not an expressive number of researches, four hypothesis are presented and validated. The findings are discussed and finally, the research limitations and the practical implications originated by this work are presented as well as topics for further researches are suggested.
Keywords: Value stream mapping; Kanban; Activity-based costing; Lean manufacturing; Textile; Lean accounting